2013
DOI: 10.1039/c2cp44572g
|View full text |Cite
|
Sign up to set email alerts
|

A rationally designed dual role anode material for lithium-ion and sodium-ion batteries: case study of eco-friendly Fe3O4

Abstract: Identifying dual role electrode materials capable of storing both lithium and sodium are thought to be highly relevant, as these materials could find potential applications simultaneously in lithium and sodium ion batteries. In this regard, the concept of dual alkali storage is demonstrated in Fe(3)O(4) anode material undergoing conversion reaction. To enable improved storage, a rational active material and electrode design is proposed. Accordingly, the following features were simultaneously incorporated into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
118
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(120 citation statements)
references
References 63 publications
1
118
1
Order By: Relevance
“…In addition to the high reversible capacity and excellent capacity retention, the could still be sustained, which exceeds most SIB anodes previously reported including nongraphitic carbon and Na-alloy metals [15][16][17][18][19][20][21][22][23][24][25][26]. After cycling at high rates, a specific capacity as high as 604 mAh g −1 can be recovered when the current density is reduced back to 0.05…”
Section: Electrochemical Measurementsmentioning
confidence: 55%
“…In addition to the high reversible capacity and excellent capacity retention, the could still be sustained, which exceeds most SIB anodes previously reported including nongraphitic carbon and Na-alloy metals [15][16][17][18][19][20][21][22][23][24][25][26]. After cycling at high rates, a specific capacity as high as 604 mAh g −1 can be recovered when the current density is reduced back to 0.05…”
Section: Electrochemical Measurementsmentioning
confidence: 55%
“…[ 384 ] While the work focused on the Na intercalation in iron oxide host materials, Hariharan et al, later, demonstrated that iron oxides provide a high specifi c capacity of ≈400 mA h g −1 through conversion reactions ( Figure 15 a), [ 385 ] forming Fe metal and Na 2 O. Nevertheless, the specifi c capacity is lower than the theoretical value of 926 mA h g −1 based on the full conversion reaction.…”
Section: Conversion Reaction Compoundsmentioning
confidence: 99%
“…Reproduced with permission. [ 385 ] Copyright 2013, Royal Society of Chemistry. b) Electrochemical charge/discharge profi les of Co 3 O 4 anodes in the voltage range between 0.01 and 2.5 V vs Na + /Na.…”
Section: Conversion Reaction Compoundsmentioning
confidence: 99%
“…[ 17,18 ] In comparison, alloying and conversion reactions are proposed for the anode materials of SIBs. [19][20][21][22] Among them Fe 2 O 3 is considered as a promising candidate for SIBs because of its abundance, low cost, high theoretical capacity (≈1007 mAh g −1 ), and nontoxic nature. [23][24][25] A wileyonlinelibrary.com…”
Section: Introductionmentioning
confidence: 99%